Micellar solubilisation enhances the antiinflammatory activities of curcumin and boswellic acids in rats with adjuvant-induced arthritis - Khayyal, Mohamed T.; El-Hazek, Rania M.; El-Sabbagh, Walaa A.; Frank, Jan; Behnam, Dariush; Abdel-Tawab, Mona (Nutrition (Burbank, Los Angeles County, Calif.), 2018)
•Micellar curcumin is much more active than the native extract in inhibiting paw edema induced by adjuvant inoculation.•Reduction in paw volume is associated with a decrease in inflammatory cytokines, C-reactive protein (CRP), and myeloperoxidase (MPO).•Micellar curcumin shows potent antioxidant activity by reducing the thiobarbituric acid reactive substances (TBARS) level and raising the total antioxidant activity.•Combining micellar curcumin with micellar boswellia markedly enhances its antiinflammatory and antioxidant activity. [Display omitted] Using advanced micellation technology, stable solubilisates of curcumin and boswellia extracts with markedly enhanced bioavailability were prepared. The drugs were given daily for 3 weeks, starting from the day of Freund complete adjuvant innoculation. Solubilized curcumin showed a reduction in paw volume, tumor necrosis factor-α, interleukin-6 and C-reactive protein, myloperoxidase and lipid peroxidation markers as well as an increase in total antioxidant capacity, an effect which wass equivalent to diclofenac. The native forms showed no significant effect compared to control untreated groups. Native extracts of curcumin and boswellia are known to exert antiinflammatory properties but have poor bioavailability when given orally. Using advanced micellation technology, it has been possible to produce stable solubilisates of these extracts with markedly enhanced bioavailability. In the present study, we compared the chronic antiinflammatory activities of native and micellar curcumin in the rat adjuvant arthritis model, using diclofenac as a reference drug. Adjuvant arthritis was induced by injecting Freund's complete adjuvant (FCA) into the right hind paw of rats and monitoring paw volume over 3 wk. The drugs were given daily for 3 wk, starting from the day of adjuvant inoculation. The serum was collected at end of the experiment for the assay of inflammatory and oxidative stress parameters. Statistical comparisons between different groups were carried out by one-way analysis of variance followed by Tukey-Kramer multiple comparison test. Solubilized curcumin showed better antiinflammatory activity than its native form. The reduction in paw volume was reflected in corresponding changes in relevant mediators of inflammation like tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), myeloperoxidase (MPO), and lipid peroxidation markers. The combination of curcumin and boswellia solubilisates synergistically produced an even more potent therapeutic effect. The findings confirm that micellar solubilisation of curcumin and boswellia not only increases their bioavailability, but also enhances their biological activity. Micellar curcumin, in particular in combination with micellar boswellia, may thus represent a promising concomitant tool for antiinflammatory treatment and a potential antiinflammatory alternative to synthetic drugs.